ANTESEDEN KONFLIK PEKERJAAN-KELUARGA DAN PENGARUHNYA TERHADAP TINGKAT KEHADIRAN DI TEMPAT KERJA (Studi Kasus UPTD Pendidikan Kecamatan Sagulung Kota Batam) - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
The purpose of this study is to obtain empirical evidence about the influence of Antecedents Work Family Conflict on the Level of Attendance at Work (Case Study UPTD Sagulung District of Batam). The population of this study is 130 female teachers in UPTD Sagulung District who teach grades 4, 5, 6 who need higher responsibility than teachers who teach in grades 1, 2, 3.The sample in this study is determined after the distribution of questionnaires, where the questionnaire is given to all the population and how many questionnaires are returned and worthy to be processed. This study used primer data which obtained by questionnaire. The result showed that involvement in work have a significant influence on the work of conflict, involvement in the affairs of the family doesn’t have a significant influence on the family conflict, involvement in work have a significant influence on the family conflict, involvement in the affairs of the family doesn’t have a significant influence on the work of conflict, expectation in a job doesn’t have a significant influence on the work on conflict, expectation in a family doesn’t have a significant influence on the family conflict, expectation in a job doesn’t have a significant influence on work family conflict, expectation in a family doesn’t have a significant influence on work family conflict, expectation in a job has a significant influence on a family conflict, conflict in a job has a significant influence on work family conflict, conflict in a family has a significant influence on work family conflict, and conflict in work family has a significant influence on the level of attendance of a person in a job.